The Adventures of Huckleberry Finn - Ho, Oliver; Andreasen, Dan; Twain, Mark, 1835-1910. (New York : Sterling Publishing, 2006)
An abridged version of the adventures of a nineteenth-century boy and a runaway slave as they float down the Mississippi River on a raft.
Keywords: Audiobooks -- English fiction; Friendship -- Fiction; Slavery -- Fiction; Voyages and travels -- Fiction